Allelic diversity of the pharmacogene CYP2D6 in New Zealand Māori and Pacific peoples - Hitchman, Leonie M.; Faatoese, Allamanda; Merriman, Tony R.; Miller, Allison L.; Liau, Yusmiati; Graham, Oscar E. E.; Kee, Ping Siu; Pearson, John F.; Fakahau, Tony; Cameron, Vicky A.; Kennedy, Martin A.; Maggo, Simran D. S. (Frontiers in Genetics, 2022)
The enzyme cytochrome P450 2D6 (CYP2D6) metabolises approximately 25% of commonly prescribed drugs, including analgesics, anti-hypertensives, and anti-depressants, among many others. Genetic variation in drug metabolising genes can alter how an individual responds to prescribed drugs, including predisposing to adverse drug reactions. The majority of research on the CYP2D6 gene has been carried out in European and East Asian populations, with Indigenous and minority populations greatly underrepresented. However, genetic variation is often population specific and analysis of diverse ethnic groups can reveal differences in alleles that may be of clinical significance. For this reason, we set out to examine the range and frequency of CYP2D6 variants in a sample of 202 Māori and Pacific people living in Aotearoa (New Zealand). We carried out a long PCR to isolate the CYP2D6 region before performing nanopore sequencing to identify all variants and alleles in these samples. We identified eleven novel variants, three of which were exonic missense variations. Six of these occurred in single samples and one was found in 19 samples (9.4% of the cohort). The remaining four novel variants were identified in two samples each. In addition, five new suballeles of CYP2D6 were identified. One striking finding was that CYP2D6*71, an allele of unknown functional status which has been rarely observed in previous studies, occurs at a relatively high frequency (9.2%) within this cohort. These data will help to ensure that CYP2D6 genetic analysis for pharmacogenetic purposes can be carried out accurately and effectively in this population group.